2020
DOI: 10.1002/pri.1888
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age and gender on acute postoperative pain and function following lumbar spine surgeries

Abstract: Background and Purpose Understanding the factors contributing to the variability in postoperative pain and function following lumbar spine surgeries (LSS) is necessary to plan inpatient rehabilitation and optimize surgical outcomes. In particular, variability due to age and gender has not been studied. This study's aim was to evaluate the variability in postoperative pain and function, during hospital stay, due to age and gender following LSS. Methods We conducted a retrospective analysis of 585 patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…20 Analogously, in a retrospective analysis of 585 patients who underwent lumbar spine surgery, Kanaan et al found male patients walked significantly longer distance than female patients, although clinically insignificant. 22 In our study, we found that age older than 75 years and females were independently related to prolonged LOS despite ERAS, which reminds us of the importance of age and gender on postoperative complications, and more attention should be paid to these patients in perioperative management to prevent postoperative complications. The increasing proportion of the aging population is generally associated with comorbidities and the postoperative complication rate following lumbar fusion surgery.…”
Section: Discussionsupporting
confidence: 60%
“…20 Analogously, in a retrospective analysis of 585 patients who underwent lumbar spine surgery, Kanaan et al found male patients walked significantly longer distance than female patients, although clinically insignificant. 22 In our study, we found that age older than 75 years and females were independently related to prolonged LOS despite ERAS, which reminds us of the importance of age and gender on postoperative complications, and more attention should be paid to these patients in perioperative management to prevent postoperative complications. The increasing proportion of the aging population is generally associated with comorbidities and the postoperative complication rate following lumbar fusion surgery.…”
Section: Discussionsupporting
confidence: 60%
“…The lack of statistical difference in pain intensity levels between female and male study patients is in agreement with findings in small retrospective [ 52 ] and prospective [ 51 ] studies in postoperative patients. Contrarily, several studies during the last decade have reported higher pain intensity levels in females after various kinds of surgery [ 42 , 43 , 45 47 ], which might, at least in part, be due to higher pain intensity levels than in our study patients. However, an extensive review based on those results [ 53 ] found no consensus regarding associations between patient gender and postoperative pain intensity.…”
Section: Discussionmentioning
confidence: 52%
“…Normal female dogs have a higher tactile sensitivity [ 48 , 49 ], and contradictory findings have been reported on mechanical and heat thresholds in normal female dogs compared to male dogs [ 49 ]. In line with this, women also tend to be more sensitive to pain [ 50 ], although the clinical significance appears to be low [ 51 ] and dependent on the interaction of multiple factors (i.e., anatomical, genetic, social) [ 52 ]. As such, in light of the relatively small study population (n = 30 dogs) of this RCT, the causes of this gender difference in clinical representation, and efficacy of the CXB-PEAM in providing analgesia and reducing interference of pain in daily activities, remain to be determined.…”
Section: Discussionmentioning
confidence: 99%